The effects of an eight-week customised endurance-training programme on running kinematics and impact associated with fatigue in recreational runners - Sackey, Saint Andrews (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.